2002
DOI: 10.1097/00000658-200203000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Metaplastic Columnar Mucosa in the Cervical Esophagus After Esophagectomy

Abstract: ObjectiveTo evaluate the pathogenesis of metaplastic processes within the esophagus using a human model in which the exact duration of reflux was known. Summary Background DataThe pathogenesis of Barrett's esophagus (BE) is incompletely understood. Patients undergoing esophagectomy and gastric tube reconstruction represent a good model for studying the pathophysiology of columnar cell metaplasia of the human esophagus because the cervical esophagus is rarely or never exposed to gastric contents before the surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
3
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 23 publications
1
82
3
6
Order By: Relevance
“…El-Serag et al (33) and Goldblum et al (34) suggest that gastroesophageal reflux disease is not a risk factor for CIM. On the other hand, Oberg et al (35) reported the development of cardiac mucosa (with some proceeding to IM) in the proximal esophagus after esophagectomy, suggesting that this is an acquired condition related to acid exposure. Interestingly, Sharma et al (16) found that there was a higher prevalence and incidence of dysplasia in their short segment BE group than in their CIM group (11.3% versus 4.6%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…El-Serag et al (33) and Goldblum et al (34) suggest that gastroesophageal reflux disease is not a risk factor for CIM. On the other hand, Oberg et al (35) reported the development of cardiac mucosa (with some proceeding to IM) in the proximal esophagus after esophagectomy, suggesting that this is an acquired condition related to acid exposure. Interestingly, Sharma et al (16) found that there was a higher prevalence and incidence of dysplasia in their short segment BE group than in their CIM group (11.3% versus 4.6%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Pleural and tracheal injury, as well as hemorrhage, may occur during mediastinal dissection due to severe periesophagitis leading to adhesions between the esophagus and mediastinal structures. It is also well known that stasis esophagitis observed in endstage disease predisposes to premalignant lesions or even carcinoma [14][15][16][17] . Based on this premises, the idea of striping the esophageal mucosa and submucosa through cervical and abdominal incisions in the absence of thoracotomy came to mind.…”
Section: History and Indicationsmentioning
confidence: 99%
“…Refluxate-containing bile acid, along with gastric acid, is considered to be more harmful, leading to inflammation, ulceration, Barrett's esophagus, and ultimately EAC. Development of Barrett's esophagus is a slow process and distinctive mucus-secreting goblet cell formation can take 5 to 10 years (21,22). Typically, EAC develops through metaplasia-dysplasia-carcinoma sequence involving genetic and epigenetic modifications, leading to uncontrolled cell proliferation, and is characterized by the presence of intestinal metaplasia with low-grade (LGD) to high-grade dysplasia (HGD), which eventually may progress to invasive carcinoma (20).…”
Section: Risk Factorsmentioning
confidence: 99%